My second home programme–Analysis of the demand and Supply. - Abdul Aziz, Abdul Rashid (Universiti Sains Malaysia, 2013)
Malaysia My Second Home Programme (MM2H) was launched in 2002 by the Malaysian government to capture the growing trend of retirees buying second homes abroad. The first objective was to analyse the MM2H takers' motivation for residing in Malaysia, their likes and dislikes about Malaysia and the locations they lived in.